2016
DOI: 10.1093/femsec/fiw251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the methanogen and bacterial communities of rumen environments: solid adherent, fluid and epimural

Abstract: The rumen microbiome occupies a central role in animal health and productivity. A better understanding of the rumen ecosystem is essential to increase productivity or decrease methane production. Samples were collected from the three main rumen environments: the solid-adherent fraction, the liquid fraction and the epithelium. For the liquid and solid fraction, two alternative sample processing protocols were compared, resulting in a total of five sample types: crude solids (S), the eluted solid-adherent fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
106
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(137 citation statements)
references
References 68 publications
29
106
1
1
Order By: Relevance
“…In addition, we found that Prevotella was the most abundant genus in the three fractions (Figures 2B, 3B, 4B). This result is consistent with findings regarding the rumen solid and liquid fractions of dairy cattle fed ryegrass or white clover (Bowen et al, 2018) and a TMR (forage:concentrate = 70:30, forage = prewilted grass and maize silage) (De Mulder et al, 2017) and the rumen contents and epithelium of dairy cattle fed a TMR (forage:concentrate = 55:45, forage = corn silage and corn stover) (Liu et al, 2016). Prevotella represents one of the most abundant genera in the rumen; this genus exhibits genetic and metabolic diversity (Bekele et al, 2010) and plays roles in carbohydrate utilization (Dehority, 1966;Cotta, 1992;Gardner et al, 1995;Kabel et al, 2011), nitrogen metabolism (Kim et al, 2017), and fiber degradation (Mayorga et al, 2016).…”
Section: Differences In Bacterial Community Structure Among the Solidsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, we found that Prevotella was the most abundant genus in the three fractions (Figures 2B, 3B, 4B). This result is consistent with findings regarding the rumen solid and liquid fractions of dairy cattle fed ryegrass or white clover (Bowen et al, 2018) and a TMR (forage:concentrate = 70:30, forage = prewilted grass and maize silage) (De Mulder et al, 2017) and the rumen contents and epithelium of dairy cattle fed a TMR (forage:concentrate = 55:45, forage = corn silage and corn stover) (Liu et al, 2016). Prevotella represents one of the most abundant genera in the rumen; this genus exhibits genetic and metabolic diversity (Bekele et al, 2010) and plays roles in carbohydrate utilization (Dehority, 1966;Cotta, 1992;Gardner et al, 1995;Kabel et al, 2011), nitrogen metabolism (Kim et al, 2017), and fiber degradation (Mayorga et al, 2016).…”
Section: Differences In Bacterial Community Structure Among the Solidsupporting
confidence: 92%
“…Desulfobulbus spp. participate in the reduction of sulfur compounds (Schären et al, 2017) and oxygen consumption (De Mulder et al, 2017), which are affected by the concentration of propionate (John Parkes and Graham Calder, 1985); these observations are consistent with the increased rumen concentration of propionate observed in the UC and LU treatments. These results indicate that the ureolytic and sulfur-reducing abilities of rumen bacteria may be affected when the nitrogen content is increased.…”
Section: Changes In the Rumen Bacteria With Urea Supplementationsupporting
confidence: 73%
See 3 more Smart Citations